History, historiography and document: the study of Jews and Christians in Antioch-on-the-Orontes (fourth century AD) - Silva, Érica Cristhyane Morais da (Romanitas - Revista de Estudos Grecolatinos, 2013)
Recently, the historiography of Christian‑Jewish relations in Late Antiquity has been an important and vital place of reflections showing change of perspective, and challenging old concepts. Our main aim in this paper is to discuss the findings related to this new trend in historical studies in order to understand the history of Christian‑Jewish relations in Antioch‑on‑the‑Orontes during the Fourth century A.D. Therefore, we will rely on an approach from the point of view of Political and Cultural History. We will also present and discuss some primary sources that are available to study this subject.
Keywords: Late Antiquity; Christianity; Judaism; Antioch on -the Orontes